2014
DOI: 10.1007/s00268-014-2847-x
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Chemoradiation Therapy Decreases the Number of Lymph Nodes Resected During Esophagectomy

Abstract: Preoperative chemoradiation decreases the number of harvested lymph nodes following esophagectomy regardless of the surgical technique used. The optimum number of lymph nodes currently recommended to be dissected for accurate nodal staging and survival needs revision in this group of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Several studies have shown that neoadjuvant treatment results in a reduced number of resected lymph nodes, whereas others have reported a lower number of metastatic lymph nodes but no reduction in the total number of lymph nodes. The introduction of neoadjuvant treatment since 2010 in the present study may have led to some distortion in the assessment of total number of lymph nodes as an QOC indicator.…”
Section: Discussionmentioning
confidence: 56%
“…Several studies have shown that neoadjuvant treatment results in a reduced number of resected lymph nodes, whereas others have reported a lower number of metastatic lymph nodes but no reduction in the total number of lymph nodes. The introduction of neoadjuvant treatment since 2010 in the present study may have led to some distortion in the assessment of total number of lymph nodes as an QOC indicator.…”
Section: Discussionmentioning
confidence: 56%
“…Besides, it was reported that neoadjuvant therapy significantly decreased the total number of lymph nodes retrieved in rectal cancer 28,29 . Issaka et al 30 also found that preoperative chemoradiation caused a significant reduction in the number of retrieved lymph nodes during esophagectomy. To assess nodal staging accurately, the NCCN guidelines have proposed at least 15 lymph nodes be dissected in patients undergoing esophagectomy with neoadjuvant treatment 31 .…”
Section: Discussionmentioning
confidence: 96%
“…Our study identified that preoperative RT is a significant factor in decreasing nodal count of NDs in patients with HNCs. The impact that preoperative RT has on lymph node count has been reported extensively in colorectal cancer and esophageal cancer . Because it has been well established that RT decreases lymph node count in other anatomical regions, a similar trend can be extrapolated and expected in HNCs.…”
Section: Discussionmentioning
confidence: 73%